Hollow glass microsphere / ferroferric oxide / carbon absorbing powder and preparation method thereof
By covering the surface of the hollow glass microbeads with iron tetraoxide and carbon layers to form a hollow glass microbead/ferric tetraoxide/carbon absorbing powder with a double-shell-double hollow structure, the problem of the single loss mechanism of the existing wave absorbing material is solved, and a high-performance electromagnetic wave absorption effect is achieved.
Patent Information
- Application Number
- CN202011602976.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-12-29
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2040-12-29
AI Technical Summary
The existing wave absorbing materials have a single loss mechanism for electromagnetic waves and cannot meet the needs of high-performance wave absorbing agents.
Hollow glass microbeads/ferrous tetraoxide/carbon absorbing powder are used to coat iron tetraoxide and carbon layers on the surface of hollow glass microbeads to form a unique bihull-double hollow structure to enhance wave absorption performance.
It realizes multiple reflection losses of electromagnetic waves in the wave-absorbing powder, improves dielectric constant and magnetic permeability, enhances wave-absorbing performance, and has excellent characteristics such as corrosion resistance and oxidation resistance.
Smart Images

Figure CN114696112B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of wave-absorbing materials, and in particular to a hollow glass microsphere / ferroferric oxide / carbon wave-absorbing powder and a preparation method thereof. Background Art
[0002] Hollow glass microspheres are hollow, lightweight, and uniformly sized spherical particles that are resistant to high and low temperatures, corrosion, insulation, heat insulation, chemical stability, high strength, and non-toxic. Although they do not have absorbing properties, if one or more layers of absorbers with good chemical stability and strong absorbing ability are coated on the surface of lightweight hollow glass microspheres, it can reduce costs, effectively utilize resources, and reduce the density of the material, thereby obtaining an ideal lightweight composite absorbing material.
[0003] There are many studies on the application of glass microspheres in the field of wave absorption:
[0004] The existing literature provides a fly ash glass microsphere / ferrite composite wave absorbing material, which has excellent wave absorbing performance by coating the fly ash glass microsphere with a specific type of ferrite. The composite wave absorbing material is light in weight and has a certain sound absorbing effect.
[0005] Another existing document provides a process for chemical plating of the surface of hollow glass microspheres. The produced metal-plated hollow glass microspheres have the advantages of complete metal layer, light weight, and good conductivity. As fillers, they can reduce material density, reduce costs, and enhance mechanical properties.
[0006] Another existing document provides a method for silver-plating the surface of hollow glass microspheres and the silver-plated hollow glass microspheres, which not only have low infrared emissivity but also have certain radar absorbing performance. Compared with pure metal particles, the cost of silver-plated hollow glass microspheres is lower. However, the problem with the above method is that the loss mechanism of electromagnetic waves is single, and its absorption performance cannot meet the existing demand for high-performance absorbers.
[0007] In view of the above problems, it is necessary to provide an absorbing material with low density, low cost, good mechanical properties and high absorbing performance. Summary of the invention
[0008] The main purpose of the present invention is to provide a hollow glass microsphere / ferroferric oxide / carbon absorbing powder and a preparation method thereof, so as to solve the problem that the existing absorbing materials have a single loss mechanism for electromagnetic waves and cannot meet the needs of high-performance absorbing agents.
[0009] In order to achieve the above-mentioned object, the present invention provides a method for preparing hollow glass microspheres / ferroferric oxide / carbon absorbing powder, comprising: step S1, preparing hollow glass microspheres / ferroferric oxide / silicon dioxide; step S2, adding the hollow glass microspheres / ferroferric oxide / silicon dioxide to an organic solvent containing polyvinyl pyrrolidone, dispersing and drying the hollow glass microspheres / ferroferric oxide / silicon dioxide to prepare modified hollow glass microspheres / ferroferric oxide / silicon dioxide; under the action of a catalyst, adding the modified hollow glass microspheres / ferroferric oxide / silicon dioxide to an inorganic solvent containing pyrrole; The hollow glass microspheres / ferroferric oxide / silicon dioxide / polypyrrole microspheres are prepared by stirring and drying the hollow glass microspheres / ferroferric oxide / silicon dioxide / polypyrrole microspheres; step S3, in an inert gas atmosphere, high-temperature calcining the hollow glass microspheres / ferroferric oxide / silicon dioxide / polypyrrole microspheres to obtain hollow glass microspheres / ferroferric oxide / silicon dioxide / carbon microspheres; the hollow glass microspheres / ferroferric oxide / silicon dioxide / carbon microspheres are added to an alkaline solution for etching, and then stirred and dried to obtain hollow glass microspheres / ferroferric oxide / carbon absorbing powders having gaps between the ferroferric oxide layer and the carbon layer.
[0010] Furthermore, step S2 specifically includes: adding hollow glass microspheres / ferroferric oxide / silicon dioxide to an organic solvent and performing ultrasonic dispersion treatment; subsequently adding polyvinyl pyrrolidone, performing ultrasonic dispersion treatment, filtering, and drying to prepare modified hollow glass microspheres / ferroferric oxide / silicon dioxide; adding the modified hollow glass microspheres / ferroferric oxide / silicon dioxide to an inorganic solvent and performing ultrasonic dispersion treatment; subsequently adding a catalyst, stirring, and then adding pyrrole, further stirring, filtering, and drying to prepare hollow glass microspheres / ferroferric oxide / silicon dioxide / polypyrrole microspheres.
[0011] Furthermore, the organic solvent is ethanol or acetone, the inorganic solvent is deionized water, and the catalyst includes ferric chloride; in the step of preparing modified hollow glass microspheres / ferroferric oxide / silicon dioxide, the hollow glass microspheres / ferroferric oxide / silicon dioxide are 1 to 6 parts by mass, the ethanol or acetone are 50 to 400 parts by mass, and the polyvinyl pyrrolidone is 3 to 8 parts by mass; in the step of preparing hollow glass microspheres / ferroferric oxide / silicon dioxide / polypyrrole microspheres, the modified hollow glass microspheres / ferroferric oxide / silicon dioxide are 1 to 6 parts by mass, the deionized water is 100 to 400 parts by mass, the ferric chloride is 5 to 10 parts by mass, and the pyrrole is 1 to 5 parts by mass.
[0012] Further, step S3 specifically includes: calcining the hollow glass microspheres / ferroferric oxide / silicon dioxide / polypyrrole microspheres under nitrogen conditions and at a temperature of 500-800°C for 2 to 6 hours to obtain hollow glass microspheres / ferroferric oxide / silicon dioxide / carbon microspheres; then dispersing the hollow glass microspheres / ferroferric oxide / silicon dioxide / carbon microspheres into 100 to 400 parts of a 10 to 30% sodium hydroxide solution for etching, stirring at a speed of 800 to 1500 r / min at 40 to 80°C for 10 to 20 hours, collecting the precipitate with a magnet, pouring out the supernatant, washing with distilled water for 3 to 6 times, and placing the precipitate in a blast oven at a temperature of 40 to 80°C for drying for 8 to 15 hours to obtain hollow glass microspheres / ferroferric oxide / carbon absorbing powder.
[0013] Further, step S1 specifically includes: sub-step S11, pre-treating the hollow glass microspheres with an alkaline solution; sub-step S12, treating Fe(CO) 5 and the pretreated hollow glass microspheres are added to an alcohol amine solvent, and stirred to obtain a reaction solution; then an alkaline solution and a reducing agent are added to the reaction solution, and the reaction solution is stirred, filtered, and dried to obtain hollow glass microspheres / ferroferric oxide with a core / shell structure; sub-step S13, the hollow glass microspheres / ferroferric oxide are added to the mixed solution for dispersion treatment; then ethyl orthosilicate is added, and the reaction solution is stirred, filtered, and dried to obtain hollow glass microspheres / ferroferric oxide / silicon dioxide with a core / shell / shell structure.
[0014] Furthermore, the alcohol amine solvent is one or more of methanolamine, ethanolamine, and diethanolamine; the alkaline solution is one or more of NaOH and KOH; the reducing agent is one or more of hydrazine hydrate and sodium hypophosphite; and the mixed solution includes anhydrous ethanol or acetone, water, and a weak alkaline solution.
[0015] Further, sub-step S12 specifically includes: Fe(CO) 5 and the pretreated hollow glass microspheres are added to an alcohol amine solvent, and stirred to obtain a reaction solution; then an alkaline solution is added to the reaction solution to maintain a pH value in the range of 8 to 10, and then a reducing agent is added to the reaction solution, and stirred to fully react to obtain a first precipitate; the first precipitate is cleaned with a first cleaning solution, and then dried to obtain hollow glass microspheres / ferroferric oxide.
[0016] Furthermore, the first cleaning solution is deionized water, the alkaline solution is NaOH solution, and the reducing agent is hydrazine hydrate; the pretreated hollow glass microspheres are 8 to 50 parts by weight, Fe(CO) 5 The mass concentration of the aqueous solution is 5 to 40 parts by mass, the mass concentration of the alcohol amine solvent is 200 to 600 parts by mass; the mass concentration of the NaOH solution is 5 to 28%, and the mass concentration of the hydrazine hydrate is 10 to 50 parts by mass.
[0017] Further, sub-step S13 specifically includes: adding hollow glass microspheres / ferroferric oxide to a mixed solution of solvent, water and weak base, and ultrasonically dispersing the mixture; then adding ethyl orthosilicate, stirring the mixture in a water bath to react the mixture to obtain a second precipitate; washing the second precipitate with a second washing liquid, and then drying the mixture to obtain hollow glass microspheres / ferroferric oxide / silicon dioxide.
[0018] Furthermore, the solvent includes anhydrous ethanol, and the weak base includes aqueous ammonia; the hollow glass microspheres / ferrosoferric oxide are 2 to 10 parts by mass, the anhydrous ethanol is 800 to 1200 parts by mass, the water is 200 to 500 parts by mass, the aqueous ammonia is 20 to 100 parts by mass, and the tetraethyl orthosilicate is 1 to 6 parts by mass.
[0019] Another aspect of the present application also provides a hollow glass microsphere / ferroferric oxide / carbon absorbing powder prepared according to the preparation method of the hollow glass microsphere / ferroferric oxide / carbon absorbing powder provided by the present application, wherein the hollow glass microsphere / ferroferric oxide / carbon absorbing powder comprises a hollow glass microsphere layer as a hollow inner core layer, and a ferroferric oxide layer and a carbon layer sequentially coated on the outer surface of the hollow inner core layer from the inside to the outside, and there is a gap between the ferroferric oxide layer and the carbon layer.
[0020] By applying the technical solution of the present invention, the hollow glass microsphere / ferroferric oxide / carbon absorbing powder has a unique double-shell-double hollow structure, which can greatly reduce the density of the absorbing powder itself, greatly realize the multiple reflection loss of electromagnetic waves inside the absorbing powder, increase the propagation path of electromagnetic waves, enrich the loss mechanism of the absorbing powder itself, and can improve the spatial polarization effect of the absorbing powder, so that the dielectric constant and magnetic permeability of the absorbing powder are significantly improved. At the same time, the absorbing powder also has excellent properties such as corrosion resistance and oxidation resistance, improves its compatibility and dispersibility with the matrix, and improves its interface bonding force, which can meet the needs of different application scenarios. In addition, the hollow glass microspheres are used as hollow inner core layers, and the preparation costs of the hollow glass microsphere layer, the ferroferric oxide layer and the carbon layer are relatively low. Therefore, the hollow glass microsphere / ferroferric oxide / carbon absorbing powder with the double-shell-double hollow structure belongs to an absorber with excellent electromagnetic properties and good physical and chemical properties, and also has the advantages of low cost, oxidation resistance and corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0022] Figure 1A schematic diagram of a process flow of a method for preparing a double-shell-double-hollow structure hollow glass microsphere / ferroferric oxide / carbon absorbing powder provided in Example 1 of the present invention is shown; and
[0023] Figure 2 A schematic structural diagram of the double-shell-double-hollow structure of hollow glass microspheres / ferroferric oxide / carbon absorbing powder provided in Example 1 is shown.
[0024] The above drawings include the following reference numerals:
[0025] 1. Hollow glass microspheres; 2. Fe 3 O 4 Layer; 3, SiO 2 layer; 4, PVP; 5, polypyrrole layer; 6, carbon layer. DETAILED DESCRIPTION
[0026] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present invention can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0027] As described in the background art, the existing absorbing materials have a single loss mechanism for electromagnetic waves and cannot meet the need for high-performance absorbers. In order to solve the above technical problems, one aspect of the present invention provides a double hollow-double core-shell structure of hollow glass microspheres / ferroferric oxide / carbon absorbing powder, the hollow glass microspheres / ferroferric oxide / carbon absorbing powder comprising a hollow glass microsphere layer as a hollow inner core layer, and a ferroferric oxide layer and a carbon layer sequentially coated on the outer surface of the hollow inner core layer from the inside to the outside, and there is a gap between the ferroferric oxide layer and the carbon layer.
[0028] The hollow glass microsphere / ferroferric oxide / carbon absorbing powder has a unique double-shell-double hollow structure, which can greatly reduce the density of the absorbing powder itself, greatly realize the multiple reflection loss of electromagnetic waves inside the absorbing powder, increase the propagation path of electromagnetic waves, enrich the loss mechanism of the absorbing powder itself, and can improve the spatial polarization effect of the absorbing powder, so that the dielectric constant and magnetic permeability of the absorbing powder are significantly improved. At the same time, the absorbing powder also has excellent properties such as corrosion resistance and oxidation resistance, improves compatibility and dispersibility with the matrix, and improves its interface bonding force, which can meet the needs of different application scenarios. In addition, there are many types of hollow materials that can be used as hollow inner core layers, and the preparation cost of hollow materials, ferroferric oxide layers and carbon layers is low. Therefore, the hollow glass microsphere / ferroferric oxide / carbon absorbing powder with the above double-shell-double hollow structure belongs to an absorber with excellent electromagnetic properties and good physical and chemical properties, and also has the advantages of low cost, oxidation resistance and corrosion resistance.
[0029] In the hollow glass microsphere / ferroferric oxide / carbon absorbing powder, the hollow glass microspheres are used as the hollow inner core layer, which can further reduce the density and cost of the absorbing material. It should be noted that the particle size range of the hollow glass microspheres refers to the particle size of existing commercially available products.
[0030] Another aspect of the present invention also provides a method for preparing a hollow glass microsphere / ferroferric oxide / carbon absorbing powder with a double hollow-dual core-shell structure, the preparation method comprising: step S1, preparing hollow glass microspheres / ferroferric oxide / silicon dioxide; step S2, adding the hollow glass microspheres / ferroferric oxide / silicon dioxide to an organic solvent containing polyvinyl pyrrolidone, dispersing and drying the hollow glass microspheres / ferroferric oxide / silicon dioxide to prepare modified hollow glass microspheres / ferroferric oxide / silicon dioxide; under the action of a catalyst, adding the modified hollow glass microspheres / ferroferric oxide / silicon dioxide to an organic solvent containing polyvinyl pyrrolidone; The method comprises the following steps: adding the hollow glass microspheres / ferroferric oxide / silicon dioxide / polypyrrole microspheres to an inorganic solvent, stirring and drying the hollow glass microspheres / ferroferric oxide / silicon dioxide / polypyrrole microspheres; step S3, calcining the hollow glass microspheres / ferroferric oxide / silicon dioxide / polypyrrole microspheres at a high temperature under an inert gas atmosphere to obtain hollow glass microspheres / ferroferric oxide / silicon dioxide / carbon microspheres; adding the hollow glass microspheres / ferroferric oxide / silicon dioxide / carbon microspheres to an alkaline solution for etching, and then stirring and drying the hollow glass microspheres / ferroferric oxide / carbon absorbing powder having a gap between the ferroferric oxide layer and the carbon layer.
[0031] The above process method and equipment are simple, pollution-free, easy to control their structure and performance, and suitable for mass production. The hollow glass microspheres / ferroferric oxide / carbon absorbing powder prepared at the same time has a unique double hollow-double core-shell structure, excellent electromagnetic properties and good physical and chemical properties, and also has the advantages of low cost, anti-oxidation and corrosion resistance.
[0032] The formation of a carbon layer outside the ferroferric oxide layer is beneficial to improving the oxidation resistance and corrosion resistance of the absorbing material. In order to further improve the uniformity of the carbon layer, preferably, step S2 specifically includes: adding hollow glass microspheres / ferroferric oxide / silicon dioxide to an organic solvent and performing ultrasonic dispersion treatment; then adding polyvinyl pyrrolidone, performing ultrasonic dispersion treatment, filtering, and drying to prepare modified hollow glass microspheres / ferroferric oxide / silicon dioxide; adding the modified hollow glass microspheres / ferroferric oxide / silicon dioxide to an inorganic solvent and performing ultrasonic dispersion treatment; then adding a catalyst, stirring, and then adding pyrrole, further stirring, filtering, and drying to prepare hollow glass microspheres / ferroferric oxide / silicon dioxide / polypyrrole (PPy) microspheres.
[0033] In order to facilitate the removal of the solvent used in the preparation process, a solvent with a lower boiling point needs to be selected. Taking into account the solvent's solubility for the raw materials, the safety of the preparation process, and the cost, preferably, the organic solvent is ethanol or acetone, and the inorganic solvent is deionized water.
[0034] In a preferred embodiment, the catalyst includes ferric chloride. Compared with other catalysts, the catalytic activity of pyrrole is higher in the presence of the above catalysts, and the catalyst is easier to remove after the reaction is completed.
[0035] In a preferred embodiment, in the step of preparing the modified hollow glass microspheres / ferroferric oxide / silicon dioxide, the hollow glass microspheres / ferroferric oxide / silicon dioxide are 1 to 6 parts by mass, ethanol or acetone are 50 to 400 parts by mass, and polyvinyl pyrrolidone is 3 to 8 parts by mass. The weight ratio of hollow glass microspheres / ferroferric oxide / silicon dioxide, organic solvent (ethanol or acetone) and polyvinyl pyrrolidone includes but is not limited to the above range, and limiting it within the above range is conducive to further improving the coating uniformity, structural stability and porosity of the subsequently formed polypyrrole layer on the surface of the silicon dioxide layer, thereby further improving the corrosion resistance, oxidation resistance and wave loss of the finally formed hollow glass microspheres / ferroferric oxide / carbon absorbing powder.
[0036] In a preferred embodiment, in the step of preparing hollow glass microspheres / ferroferric oxide / silicon dioxide / polypyrrole microspheres, the modified hollow glass microspheres / ferroferric oxide / silicon dioxide are 1 to 6 parts by mass, deionized water is 100 to 400 parts by mass, ferric chloride is 5 to 10 parts by mass, and pyrrole is 1 to 5 parts by mass. The weight ratio of the modified hollow glass microspheres / ferroferric oxide / silicon dioxide, deionized water, ferric chloride and pyrrole includes but is not limited to the above range, and limiting it within the above range is conducive to further improving the coating uniformity and coating amount of the polypyrrole layer, thereby helping to improve the wave loss and mechanical properties of the hollow glass microspheres / ferroferric oxide / carbon absorbing powder.
[0037] In one embodiment of the present invention, step S3 specifically includes: calcining hollow glass microspheres / ferroferric oxide / silicon dioxide / polypyrrole microspheres under nitrogen conditions and at a temperature of 500-800°C for 2-6 hours to obtain hollow glass microspheres / ferroferric oxide / silicon dioxide / carbon microspheres; then dispersing the hollow glass microspheres / ferroferric oxide / silicon dioxide / carbon microspheres into 100-400 parts of a 10-30% sodium hydroxide solution for etching, stirring at a speed of 800-1500r / min at 40-80°C for 10-20 hours, collecting the precipitate with a magnet, pouring out the supernatant, washing with distilled water for 3-6 times, and placing the precipitate in a blast oven at a temperature of 40-80°C for drying for 8-15 hours to obtain hollow glass microspheres / ferroferric oxide / carbon absorbing powder. Limiting the calcination temperature within the above range is conducive to further improving the porosity of the absorbing material, thereby further reducing the density of the absorbing material and the loss of the wave. Limiting the concentration of sodium hydroxide, the temperature, the rotation speed and the time of the etching process within the above range is conducive to further improving the porosity between the ferroferric oxide layer and the carbon layer, thereby further improving the loss of the hollow glass microsphere / ferroferric oxide / carbon absorbing powder. Limiting the temperature and time of the drying process within the above range is conducive to improving the drying efficiency and shortening the preparation cycle.
[0038] In one embodiment of the present invention, step S1 specifically includes: sub-step S11, pre-treating the hollow glass microspheres with an alkaline solution; sub-step S12, treating Fe(CO) 5 The hollow glass microspheres after pretreatment are added to the alcohol amine solvent, and the reaction solution is obtained after stirring;Then the alkaline solution and the reducing agent are added to the reaction solution, and the hollow glass microspheres / ferroferric oxide of the core / shell structure are obtained after stirring, filtering and drying. Wherein, the hollow glass microspheres / ferroferric oxide of the core / shell structure refer to the ferroferric oxide generated by the reaction coated on the outer surface of the hollow glass microspheres;Sub-step S13, hollow glass microspheres / ferroferric oxide are added to the mixed solution for dispersion treatment;Then ethyl orthosilicate is added, and the hollow glass microspheres / ferroferric oxide / silicon dioxide of the core / shell / shell structure are obtained after stirring, filtering and drying. Wherein, the hollow glass microspheres / ferroferric oxide / silicon dioxide of the core / shell / shell structure refer to the ferroferric oxide coated on the outer surface of the hollow glass microspheres, and the silicon dioxide generated by the reaction is coated on the outer surface of the ferroferric oxide.
[0039] In a non-limiting embodiment, the alcohol amine solvent is one or more of methanolamine, ethanolamine, and diethanolamine.
[0040] The above-mentioned alcohol amine solvents are all weakly alkaline, and using them as solvents is beneficial to further improve Fe(CO) 5The reaction rate is increased, which is beneficial to further improve the conversion rate of ferric hydroxide, thereby improving the absorbing performance of the absorbing material. The amount of the alcoholamine solution is not specifically limited and can be adjusted as needed.
[0041] In the above sub-step S11, the alkali solution may be any type commonly used in the art, such as NaOH and / or KOH.
[0042] In one embodiment of the present invention, the reducing agent is hydrazine hydrate and / or sodium hypophosphite. Compared with other reducing agents, the above reducing agents have weaker reducing properties, so the use of the above reducing agents in the reduction reaction can convert iron trioxide into iron tetroxide.
[0043] In one embodiment of the present invention, the mixed solution includes anhydrous ethanol, acetone, water, and a weak base solution. In a preferred embodiment, the weak base solution is ammonia water.
[0044] In one embodiment of the present invention, sub-step S12 specifically includes: Fe(CO) 5 and the pretreated hollow glass microspheres are added to an alcohol amine solvent, and stirred to obtain a reaction solution; then an alkaline solution is added to the reaction solution to maintain a pH value in the range of 8 to 10, and then a reducing agent is added to the reaction solution, and stirred to fully react to obtain a first precipitate; the first precipitate is cleaned with a first cleaning solution, and then dried to obtain hollow glass microspheres / ferroferric oxide.
[0045] During the above coating process, Fe(CO) 5 It is unstable and will form ferric oxide after contacting with a solvent. The generated ferric oxide reacts with a reducing agent to reduce part of the ferric oxide to ferrous oxide, thereby obtaining a ferroferric oxide coating layer. The formation of a ferroferric oxide layer on the surface of the hollow material using the above preparation method is conducive to improving the uniformity of the ferroferric oxide coating layer, thereby further improving the performance stability and uniformity of the absorbing material.
[0046] In a preferred embodiment, the first cleaning solution is deionized water, the alkaline solution is NaOH solution, and the reducing agent is hydrazine hydrate; the pretreated hollow glass microspheres are 8 to 50 parts by weight, Fe(CO) 5 The mass concentration of the NaOH solution is 5-28%, and the mass concentration of hydrazine hydrate is 10-50 parts by mass. 5 Limiting the weight ratio of the iron tetroxide to the above range is beneficial to further improve the conversion rate of iron tetroxide, thereby further improving the absorbing performance of the absorbing material.
[0047] In a preferred embodiment, sub-step S13 specifically includes: adding hollow glass microspheres / ferroferric oxide to a mixed solution of solvent, water and weak base, and ultrasonically dispersing; then adding ethyl orthosilicate, stirring in a water bath to react to obtain a second precipitate; washing the second precipitate with a second cleaning solution, and then drying to obtain hollow glass microspheres / ferroferric oxide / silicon dioxide.
[0048] In order to further improve the coverage rate and coverage amount of the silicon dioxide layer, and further improve the wave loss rate of the subsequently prepared hollow glass microspheres / ferroferric oxide / carbon absorbing powder, preferably, the solvent includes anhydrous ethanol and the weak base includes ammonia water; the hollow glass microspheres / ferroferric oxide are 2 to 10 parts by mass, the anhydrous ethanol is 800 to 1200 parts by mass, the water is 200 to 500 parts by mass, the ammonia water is 20 to 100 parts by mass, and the tetraethyl orthosilicate is 1 to 6 parts by mass.
[0049] Another aspect of the present invention provides an absorbing device, comprising an absorbing material, wherein the absorbing material comprises the hollow glass microspheres / ferroferric oxide / carbon absorbing powder with a double hollow-double core-shell structure provided by the present invention, or the hollow glass microspheres / ferroferric oxide / carbon absorbing powder with a double hollow-double core-shell structure prepared by the preparation method provided by the present invention.
[0050] Since the hollow glass microspheres / ferroferric oxide / carbon absorbing powder with the above double hollow-double core-shell structure have excellent electromagnetic properties and good physical and chemical properties, and also have the advantages of low cost, oxidation resistance and corrosion resistance, etc. Therefore, the use of the hollow glass microspheres / ferroferric oxide / carbon absorbing powder with the double shell-double hollow structure provided by the present invention to prepare an absorbing device can greatly improve the absorbing performance and absorbing stability of the absorbing device.
[0051] The present invention is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed by the present invention.
[0052] Comparative Example 1
[0053] 1. Preparation of hollow glass microspheres / ferroferric oxide particles
[0054] 1.1 Pretreatment of hollow glass microspheres
[0055] Weigh 60 parts of hollow glass microspheres, place them in a 40% NaOH solution, ultrasonically treat for 400 minutes, then wash them with water 5 times, put the cleaned hollow glass microspheres in a 120°C forced air oven for drying for 12 hours and set aside for later use, thus completing the pretreatment of the hollow glass microspheres.
[0056] 1.2 Preparation of hollow glass microspheres / ferroferric oxide
[0057] 30 parts of pretreated hollow glass microspheres and 25 parts of oily liquid Fe(CO) 5 Add to 400 parts of alcohol amine solvent as the reaction liquid, stir evenly at a speed of 400r / min; prepare a sodium hydroxide solution with a concentration of 15% as the pH adjusting liquid of the reaction liquid. Add the pH adjusting liquid dropwise to the reaction liquid, control the pH within the range of 9, then add 30 parts of hydrazine hydrate (85%) to the reaction liquid, and continue stirring in a 14°C oil bath at a speed of 1000r / min for 3 hours. After the reaction is completed, collect the black precipitate with a magnet, pour out the supernatant, wash with deionized water and anhydrous ethanol for 5 times respectively, and after washing, put the precipitate into a 60°C blast oven for drying for 12 hours to complete the preparation of hollow glass microspheres / ferroferric oxide.
[0058] Example 1
[0059] A method for preparing hollow glass microspheres / ferroferric oxide / carbon absorbing powder with a unique double hollow-dual core-shell structure, the process flow is as follows Figure 1 As shown, the schematic diagram of the structure of the absorber is shown in Figure 2 (1 represents hollow glass microspheres, 2 represents Fe 3 O 4 layer, 3 represents SiO 2 layer, 4 represents PVP, 5 represents polypyrrole layer, 6 represents carbon layer), comprising the following steps:
[0060] 1. Preparation of hollow glass microspheres / ferroferric oxide particles
[0061] 1.1 Pretreatment of hollow glass microspheres
[0062] Weigh 60 parts of hollow glass microspheres, place them in a 40% NaOH solution, ultrasonically treat for 400 minutes, then wash them with water 5 times, put the cleaned hollow glass microspheres in a 120°C forced air oven for drying for 12 hours and set aside for later use, thus completing the pretreatment of the hollow glass microspheres.
[0063] 1.2 Hollow glass microspheres / Fe 3 O 4 Preparation
[0064] 30 parts of pretreated hollow glass microspheres and 25 parts of oily liquid Fe(CO) 5Add to 400 parts of alcohol amine solvent as the reaction liquid, stir evenly at a speed of 400r / min; prepare a sodium hydroxide solution with a concentration of 15% as the pH adjusting liquid of the reaction liquid. Add the pH adjusting liquid dropwise to the reaction liquid, control the pH within the range of 9, then add 30 parts of hydrazine hydrate (85%) to the reaction liquid, and continue stirring in a 14°C oil bath at a speed of 1000r / min for 3 hours. After the reaction is completed, collect the black precipitate with a magnet, pour out the supernatant, wash with deionized water and anhydrous ethanol for 5 times respectively, and after washing, put the precipitate into a 60°C blast oven for drying for 12 hours to complete the preparation of hollow glass microspheres / ferroferric oxide.
[0065] 2. Preparation of double hollow-double core-shell hollow glass microspheres / ferroferric oxide / carbon absorbing powder
[0066] 2.1 Preparation of hollow glass microspheres / ferroferric oxide / silicon dioxide
[0067] 10 parts of the prepared hollow glass microspheres / Fe 3 0 4 Add to a mixed solution of 1200 parts of anhydrous ethanol, 500 parts of water and 100 parts of ammonia water with a mass concentration of 28wt%, ultrasonically treat for 30 minutes, so that the pretreated hollow glass microspheres / ferroferric oxide particles can be evenly dispersed in the solution, and then drop 1 part of ethyl orthosilicate into the solution, and stir continuously for 3 hours in a water bath at 40°C at a speed of 400r / min. After the reaction is completed, collect the precipitate with a magnet, pour out the supernatant, wash with ethanol 5 times, and put the precipitate into a 60°C blast oven for drying for 12 hours to complete the preparation of hollow glass microspheres / ferroferric oxide / silicon dioxide.
[0068] 2.2 Modification of hollow glass microspheres / ferroferric oxide / silicon dioxide
[0069] Disperse 6 parts of hollow glass microspheres / ferroferric oxide / silicon dioxide in 400 parts of ethanol solution and ultrasonicate for 20 minutes, then add 3 parts of PVP (polyvinyl pyrrolidone), continue ultrasonication for 50 minutes, and then wash with distilled water for 5 times for standby use. Then, place the washed precipitate in a 60°C forced air oven and dry it for 12 hours to complete the modification of hollow glass microspheres / ferroferric oxide / silicon dioxide.
[0070] 2.2 Preparation of hollow glass microspheres / ferroferric oxide / carbon absorbing powder
[0071] Disperse 6 parts of PVP-modified hollow glass microspheres / ferroferric oxide / silicon dioxide into 400 parts of deionized water, add 5 parts of ferric chloride after ultrasonic treatment for 20 minutes, add 1 part of pyrrole after stirring for 30 minutes, and react at a speed of 600r / min for 6 hours under stirring in a 40°C water bath. After the reaction is completed, collect the precipitate with a magnet, pour out the supernatant, wash it with distilled water and ethanol for 5 times respectively, and dry the precipitate in a blast oven at 60°C for 12 hours to obtain hollow glass microspheres / ferroferric oxide / silicon dioxide / PPy (polypyrrole) microspheres.
[0072] The obtained hollow glass microspheres / ferroferric oxide / silicon dioxide / PPy (polypyrrole) microspheres were calcined at 500°C for 2 hours under nitrogen conditions in a tubular furnace, and then the obtained hollow glass microspheres / ferroferric oxide / silicon dioxide / carbon microspheres were dispersed in 100 parts of a 15% sodium hydroxide solution for etching, and stirred at 1000 r / min for 10 hours at 60°C. The precipitate was collected with a magnet, the supernatant was poured out, and the precipitate was washed with distilled water for 5 times. The precipitate was placed in a blast oven at 60°C and dried for 12 hours to obtain a hollow glass microsphere / ferroferric oxide / carbon absorbing powder with a double hollow-double core-shell structure.
[0073] Example 2
[0074] A method for preparing hollow glass microspheres / ferroferric oxide / carbon absorbing powder with a unique double hollow-double core-shell structure comprises the following steps:
[0075] 1. Preparation of hollow glass microspheres / ferroferric oxide particles
[0076] 1.1 Pretreatment of hollow glass microspheres
[0077] Same as Example 1.
[0078] 1.2 Preparation of hollow glass microspheres / ferroferric oxide
[0079] Same as Example 1.
[0080] 2. Preparation of double hollow-double core-shell hollow glass microspheres / ferroferric oxide / carbon absorbing powder
[0081] 2.1 Preparation of hollow glass microspheres / ferroferric oxide / silicon dioxide
[0082] 6 parts of the prepared hollow glass microspheres / ferroferric oxide were added to a mixed solution of 1000 parts of anhydrous ethanol, 400 parts of water and 600 parts of ammonia water with a mass concentration of 28wt%, and ultrasonically treated for 40 minutes to make the pretreated hollow glass microspheres / ferroferric oxide particles evenly dispersed in the solution, and then 3 parts of ethyl orthosilicate were dropped into the solution, and stirred continuously for 4 hours in a water bath at 600r / min. After the reaction was completed, the precipitate was collected with a magnet, the supernatant was poured out, washed with ethanol 5 times, and the precipitate was placed in a 60°C blast oven for drying for 12 hours to complete the preparation of hollow glass microspheres / ferroferric oxide / silicon dioxide.
[0083] 2.2 Modification of hollow glass microspheres / ferroferric oxide / silicon dioxide
[0084] Disperse 3 parts of hollow glass microspheres / ferroferric oxide / silicon dioxide in 200 parts of ethanol solution and ultrasonicate for 30 minutes, then add 6 parts of PVP (polyvinyl pyrrolidone), continue ultrasonication for 50 minutes, and then wash 5 times with distilled water for standby use. Then, place the washed precipitate in a 60°C forced air oven and dry it for 12 hours to complete the modification of hollow glass microspheres / ferroferric oxide / silicon dioxide.
[0085] 2.3 Preparation of hollow glass microspheres / ferroferric oxide / carbon absorbing powder
[0086] Disperse 4 parts of PVP-modified hollow glass microspheres / ferroferric oxide / silicon dioxide into 200 parts of deionized water, add 80 parts of ferric chloride after ultrasonic treatment for 20 minutes, add 3 parts of pyrrole after stirring for 60 minutes, and react at a speed of 600r / min for 10 hours in a 40°C water bath with stirring. After the reaction is completed, collect the precipitate with a magnet, pour out the supernatant, wash it with distilled water and ethanol for 5 times respectively, and dry the precipitate in a blast oven at 60°C for 12 hours to obtain hollow glass microspheres / ferroferric oxide / silicon dioxide / PPy (polypyrrole) microspheres.
[0087] The obtained hollow glass microspheres / ferroferric oxide / silicon dioxide / PPy (polypyrrole) microspheres were calcined at 600°C for 4 hours under nitrogen conditions in a tubular furnace, and then the obtained hollow glass microspheres / ferroferric oxide / silicon dioxide / carbon microspheres were dispersed in 300 parts of a 20% sodium hydroxide solution for etching, and stirred at 1200 r / min at 60°C for 15 hours. The precipitate was collected with a magnet, the supernatant was poured out, and the precipitate was washed with distilled water for 5 times. The precipitate was placed in a blast oven at 60°C and dried for 12 hours to obtain a hollow glass microsphere / ferroferric oxide / carbon absorbing powder with a double hollow-double core-shell structure.
[0088] Example 3
[0089] A method for preparing hollow glass microspheres / ferroferric oxide / carbon absorbing powder with a unique double hollow-double core-shell structure comprises the following steps:
[0090] 1. Preparation of hollow glass microspheres / ferroferric oxide particles
[0091] 1.1 Pretreatment of hollow glass microspheres
[0092] Same as Example 1.
[0093] 1.2 Hollow glass microspheres / Fe 3 O 4 Preparation
[0094] Same as Example 1.
[0095] 2. Preparation of hollow glass microspheres / ferroferric oxide / carbon absorbing powder with double hollow-dual core-shell structure
[0096] 2.1 Preparation of hollow glass microspheres / ferroferric oxide / silicon dioxide
[0097] Two parts of the prepared hollow glass microspheres / ferroferric oxide were added to a mixed solution of 800 parts of anhydrous ethanol, 200 parts of water and 40 parts of ammonia water with a mass concentration of 28wt%, and ultrasonically treated for 50 minutes to make the pretreated hollow glass microspheres / ferroferric oxide particles evenly dispersed in the solution, and then 6 parts of ethyl orthosilicate were dropped into the solution, and stirred continuously for 6 hours in a water bath at 80°C at a speed of 1000r / min. After the reaction was completed, the precipitate was collected with a magnet, the supernatant was poured out, washed with ethanol 5 times, and the precipitate was placed in a 60°C blast oven for drying for 12 hours to complete the preparation of hollow glass microspheres / ferroferric oxide / silicon dioxide.
[0098] 2.2 Modification of hollow glass microspheres / ferroferric oxide / silicon dioxide
[0099] Disperse 1 part of hollow glass microspheres / ferroferric oxide / silicon dioxide in 50 parts of ethanol solution and ultrasonicate for 40 minutes, then add 8 parts of PVP (polyvinyl pyrrolidone), continue ultrasonication for 60 minutes, then wash with distilled water 5 times for standby use, then dry the washed precipitate in a 60°C forced air oven for 12 hours to complete the modification of hollow glass microspheres / ferroferric oxide / silicon dioxide.
[0100] 2.3 Preparation of hollow glass microspheres / ferroferric oxide / carbon absorbing powder
[0101] Disperse 1 part of PVP-modified hollow glass microspheres / ferroferric oxide / silicon dioxide into 100 parts of deionized water, add 10 parts of ferric chloride after ultrasonic treatment for 50 minutes, add 5 parts of pyrrole after stirring for 80 minutes, and react at a speed of 800r / min for 12 hours under stirring in a 50°C water bath. After the reaction is completed, collect the precipitate with a magnet, pour out the supernatant, wash it with distilled water and ethanol for 5 times respectively, and dry the precipitate in a blast oven at 60°C for 12 hours to obtain hollow glass microspheres / ferroferric oxide / silicon dioxide / PPy (polypyrrole) microspheres.
[0102] The obtained hollow glass microspheres / ferroferric oxide / silicon dioxide / PPy (polypyrrole) microspheres were calcined at 800°C for 6 hours under nitrogen conditions in a tubular furnace, and then the obtained hollow glass microspheres / ferroferric oxide / silicon dioxide / carbon microspheres were dispersed in 400 parts of a 20% sodium hydroxide solution for etching, stirred at 1500 r / min at 60°C for 20 hours, and the precipitate was collected with a magnet. The supernatant was poured out, washed with distilled water for 5 times, and the precipitate was placed in a blast oven at 60°C for 12 hours to obtain a hollow glass microsphere / ferroferric oxide / carbon absorbing powder with a double hollow-double core-shell structure.
[0103] Example 4
[0104] A method for preparing hollow glass microspheres / ferroferric oxide / carbon absorbing powder with a unique double hollow-double core-shell structure comprises the following steps:
[0105] 1. Preparation of hollow glass microspheres / ferroferric oxide particles
[0106] 1.1 Pretreatment of hollow glass microspheres
[0107] Weigh 100 parts of hollow glass microspheres, place them in a 40% NaOH solution, ultrasonically treat them for 80 minutes, then wash them with water for 5 times, and dry the cleaned hollow glass microspheres in a 120°C forced air oven for 12 hours for standby use. At this time, the pretreatment of the hollow glass microspheres is completed.
[0108] 1.2 Preparation of hollow glass microspheres / ferroferric oxide
[0109] 50 parts of pretreated hollow glass microspheres and 5 parts of oily liquid Fe(CO) 5Add to 200 parts of alcohol amine solvent as the reaction liquid, stir evenly at a speed of 200r / min; prepare a 5% sodium hydroxide solution as the pH adjusting liquid of the reaction liquid. Add the pH adjusting liquid dropwise to the reaction liquid, control the pH within the range of 8, then add 10 parts of hydrazine hydrate (85%) to the reaction liquid, and continue stirring in a 120°C oil bath at a speed of 800r / min for 2 hours. After the reaction is completed, collect the black precipitate with a magnet, pour out the supernatant, wash with deionized water and anhydrous ethanol for 5 times respectively, and after washing, put the precipitate into a 60°C blast oven for drying for 12 hours to complete the preparation of hollow glass microspheres / ferroferric oxide.
[0110] 2. Preparation of hollow glass microspheres / ferroferric oxide / carbon absorbing powder with double hollow-dual core-shell structure
[0111] 2.1 Preparation of hollow glass microspheres / ferroferric oxide / silicon dioxide
[0112] Same as Example 2.
[0113] 2.2 Modification of hollow glass microspheres / ferroferric oxide / silicon dioxide
[0114] Same as Example 2.
[0115] 2.3 Preparation of hollow glass microspheres / ferroferric oxide / carbon absorbing powder
[0116] Same as Example 2.
[0117] Example 5
[0118] A method for preparing hollow glass microspheres / ferroferric oxide / carbon absorbing powder with a unique double hollow-double core-shell structure comprises the following steps:
[0119] 1. Preparation of hollow glass microspheres / ferroferric oxide particles
[0120] 1.1 Pretreatment of hollow glass microspheres
[0121] Weigh 40 parts of hollow glass microspheres, place them in a 50% NaOH solution, ultrasonically treat for 80 minutes, and then wash them with water for 5 times. Put the cleaned hollow glass microspheres in a 120°C forced air oven for drying for 12 hours and set aside for use. At this time, the pretreatment of the hollow glass microspheres is completed.
[0122] 1.2 Preparation of hollow glass microspheres / ferroferric oxide
[0123] 8 parts of pretreated hollow glass microspheres and 40 parts of oily liquid Fe(CO) 5Add to 600 parts of alcohol amine solvent as the reaction liquid, stir evenly at a speed of 500r / min; prepare a sodium hydroxide solution with a concentration of 20% as the pH adjusting liquid of the reaction liquid. Add the pH adjusting liquid dropwise to the reaction liquid, control the pH within the range of 10, then add 50 parts of hydrazine hydrate (85%) to the reaction liquid, and continue stirring in a 160°C oil bath pot at a speed of 1500r / min for 4 hours. After the reaction is completed, collect the black precipitate with a magnet, pour out the supernatant, wash with deionized water and anhydrous ethanol for 5 times respectively, and after washing, put the precipitate into a 60°C blast oven for drying for 12 hours to complete the preparation of hollow glass microspheres / ferroferric oxide.
[0124] 2. Preparation of hollow glass microspheres / ferroferric oxide / carbon absorbing powder with double hollow-dual core-shell structure
[0125] 2.1 Preparation of hollow glass microspheres / ferroferric oxide / silicon dioxide
[0126] Same as Example 2.
[0127] 2.2 Modification of hollow glass microspheres / ferroferric oxide / silicon dioxide
[0128] Same as Example 2.
[0129] 2.3 Preparation of hollow glass microspheres / ferroferric oxide / carbon absorbing powder
[0130] Same as Example 2.
[0131] The original hollow glass microspheres and the hollow glass microspheres / ferroferric oxide / carbon absorbing powders prepared in Examples 1 to 5 and Comparative Example 1 were mixed with paraffin wax to prepare 80% coaxial samples and tested. The main steps are: first, the hollow glass microspheres / ferroferric oxide / carbon absorbing powders were mixed with paraffin wax in a ratio of 8:2, and heated in a high-temperature oven at 65°C for 10 minutes; then quickly taken out and mixed and stirred evenly to form a viscous solid; the above viscous solid was filled into a coaxial ring mold (mold outer diameter 7mm, inner diameter 3.04mm), and samples with a thickness of 1 to 2mm were prepared respectively, and then the complex dielectric constant and complex magnetic permeability were measured by a network vector analyzer; then, according to the electromagnetic field transmission line theory, the reflection loss of the test sample at a thickness of 2.5mm was calculated by Matlab simulation. The frequency curve of the change.
[0132] The tap density of the original hollow glass microspheres and the hollow glass microspheres / ferroferric oxide / carbon absorbing powder prepared in Examples 1 to 5 and Comparative Example 1 was measured using a tap density meter. The original hollow glass microspheres and the hollow glass microspheres / ferroferric oxide / carbon absorbing powder prepared in Examples 1 to 5 and Comparative Example 1 were added to 25% dilute hydrochloric acid, and the time for the solution to generate bubbles or change color was observed. The test results are shown in Table 1.
[0133] Table 1
[0134] Example ε′(4GHz) μ′(4GHz) Frequency (GHz) Absorption peak(dB) Bandwidth (≤8 dB) Tap density Acid corrosion resistance (color) <![CDATA[Particulate Fe 3 O 4 > 9.6 1.73 5.31 -12.3 0.93 2.84 21min Comparative Example 1 8.5 1.64 5.23 -11.8 0.89 1.63 35min Example 1 18.7 3.71 3.65 -16.1 2.64 1.32 223min Example 2 21.7 3.69 3.21 -29.4 3.16 1.03 237min Example 3 26.7 3.46 3.14 -26.7 2.78 1.28 241min Example 4 16.3 3.24 3.53 -19.6 2.49 1.11 239min Example 5 29.3 3.78 3.16 -23.1 2.81 1.15 245min
[0135] By using Fe 3 O 4 Particle comparison, the powders prepared in Examples 1-5 and Comparative Example 1 were tested and found to have a higher density than the powders in Examples 1-5 and Comparative Example 1. 3 O 4 The corrosion resistance is greatly reduced, and the corrosion resistance is significantly improved; after the double shell-double hollow is formed in Example 2-5, the electromagnetic parameters, absorption bandwidth and absorption intensity of the powder are greatly improved compared with the powder performance in Example 1 and Example 1. This is because the double shell-double hollow structure greatly increases the multiple reflection loss mechanism, improves the dielectric constant and magnetic permeability, and the absorbing powder prepared in Example 1-5, with the Fe 3 O 4 As the thickness of the coating layer increases, the dielectric constant and the magnetic permeability tend to increase. As the thickness of the carbon material coating layer increases, the dielectric constant tends to increase and the magnetic permeability tends to decrease. In order to obtain excellent electromagnetic absorption performance, the material loss and impedance matching should be considered at the same time. After adjusting the formula, it is found that the material loss and impedance matching of Example 2 can reach the optimal state, and the bandwidth and absorption intensity are the best at this time.
[0136] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those described herein, for example.
[0137] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing hollow glass microspheres / ferroferric oxide / carbon absorbing powder, characterized in that: include: Step S1, preparing hollow glass microspheres / ferroferric oxide / silicon dioxide; Step S2, adding the hollow glass microspheres / ferroferric oxide / silicon dioxide to an organic solvent containing polyvinyl pyrrolidone, dispersing and drying to prepare modified hollow glass microspheres / ferroferric oxide / silicon dioxide; adding the modified hollow glass microspheres / ferroferric oxide / silicon dioxide to an inorganic solvent containing pyrrole under the action of a catalyst, stirring and drying to prepare hollow glass microspheres / ferroferric oxide / silicon dioxide / polypyrrole microspheres; Step S3, calcining the hollow glass microspheres / ferroferric oxide / silicon dioxide / polypyrrole microspheres at high temperature under an inert gas atmosphere to obtain hollow glass microspheres / ferroferric oxide / silicon dioxide / carbon microspheres; The hollow glass microspheres / ferroferric oxide / silicon dioxide / carbon microspheres are added to an alkaline solution for etching, and then stirred and dried to obtain hollow glass microspheres / ferroferric oxide / carbon absorbing powders with gaps between the ferroferric oxide layer and the carbon layer.
2. The method for preparing the hollow glass microsphere / ferroferric oxide / carbon absorbing powder according to claim 1, characterized in that: The step S2 specifically includes: The hollow glass microspheres / ferroferric oxide / silicon dioxide are added to an organic solvent and subjected to ultrasonic dispersion treatment; polyvinyl pyrrolidone is then added, subjected to ultrasonic dispersion treatment, filtered, and dried to prepare modified hollow glass microspheres / ferroferric oxide / silicon dioxide; The modified hollow glass microspheres / ferroferric oxide / silicon dioxide are added to an inorganic solvent and subjected to ultrasonic dispersion treatment; a catalyst is then added, pyrrole is added after stirring, and hollow glass microspheres / ferroferric oxide / silicon dioxide / polypyrrole microspheres are prepared after further stirring, filtering and drying.
3. The method for preparing the hollow glass microsphere / ferroferric oxide / carbon absorbing powder according to claim 2, characterized in that: The organic solvent is ethanol or acetone, the inorganic solvent is deionized water, and the catalyst includes ferric chloride; In the step of preparing the modified hollow glass microspheres / ferroferric oxide / silicon dioxide, the hollow glass microspheres / ferroferric oxide / silicon dioxide are 1 to 6 parts by mass, the ethanol or acetone is 50 to 400 parts by mass, and the polyvinyl pyrrolidone is 3 to 8 parts by mass; In the step of preparing hollow glass microspheres / ferroferric oxide / silicon dioxide / polypyrrole microspheres, the modified hollow glass microspheres / ferroferric oxide / silicon dioxide are 1 to 6 parts by mass, the deionized water is 100 to 400 parts by mass, the ferric chloride is 5 to 10 parts by mass, and the pyrrole is 1 to 5 parts by mass.
4. The method for preparing the hollow glass microsphere / ferroferric oxide / carbon absorbing powder according to claim 1, characterized in that: The step S3 specifically includes: The hollow glass microspheres / ferroferric oxide / silicon dioxide / polypyrrole microspheres are calcined under nitrogen at 500-800° C. for 2-6 hours to obtain hollow glass microspheres / ferroferric oxide / silicon dioxide / carbon microspheres; The hollow glass microspheres / ferroferric oxide / silicon dioxide / carbon microspheres are then dispersed in 100 to 400 parts of a 10 to 30% sodium hydroxide solution for etching, stirred at 800 to 1500 r / min for 10 to 20 hours at 40 to 80° C., the precipitate is collected with a magnet, the supernatant is poured out, washed with distilled water for 3 to 6 times, and the precipitate is placed in a blast oven at 40 to 80° C. for drying for 8 to 15 hours to obtain hollow glass microspheres / ferroferric oxide / carbon absorbing powder.
5. The method for preparing hollow glass microspheres / ferroferric oxide / carbon absorbing powder according to claim 1, characterized in that: The step S1 specifically includes: Sub-step S11, pre-treating the hollow glass microspheres with an alkaline solution; Sub-step S12, adding Fe(CO)5 and pretreated hollow glass microspheres to an alcohol amine solvent, stirring to obtain a reaction solution; then adding an alkaline solution and a reducing agent to the reaction solution, stirring, filtering, and drying to obtain hollow glass microspheres / ferroferric oxide with a core / shell structure; Sub-step S13, adding the hollow glass microspheres / ferroferric oxide to the mixed solution for dispersion treatment; then adding ethyl orthosilicate, stirring, filtering, and drying to obtain hollow glass microspheres / ferroferric oxide / silicon dioxide with a core / shell / shell structure.
6. The method for preparing the hollow glass microsphere / ferroferric oxide / carbon absorbing powder according to claim 5, characterized in that: The alcohol amine solvent is one or more of methanolamine, ethanolamine and diethanolamine; The alkaline solution is one or more of NaOH and KOH; The reducing agent is one or more of hydrazine hydrate and sodium hypophosphite; The mixed solution includes anhydrous ethanol or acetone, water, and a weak alkaline solution.
7. The method for preparing the hollow glass microsphere / ferroferric oxide / carbon absorbing powder according to claim 5, characterized in that: The sub-step S12 specifically includes: Adding Fe(CO)5 and pretreated hollow glass microspheres into an alcoholamine solvent, stirring to obtain a reaction solution; Subsequently, an alkaline solution is added to the reaction solution to maintain the pH value within the range of 8 to 10, and then a reducing agent is added to the reaction solution, and the reaction solution is stirred to allow it to react fully to obtain a first precipitate; the first precipitate is cleaned with a first cleaning solution, and then dried to obtain the hollow glass microspheres / ferroferric oxide.
8. The method for preparing the hollow glass microsphere / ferroferric oxide / carbon absorbing powder according to claim 7, characterized in that: The first cleaning solution is deionized water, the alkaline solution is NaOH solution, and the reducing agent is hydrazine hydrate; The pretreated hollow glass microspheres are 8 to 50 parts by mass, the Fe(CO)5 is 5 to 40 parts by mass, the alcohol amine solvent is 200 to 600 parts by mass; the mass concentration of the NaOH solution is 5 to 28%, and the hydrazine hydrate is 10 to 50 parts by mass.
9. The method for preparing the hollow glass microsphere / ferroferric oxide / carbon absorbing powder according to claim 5, characterized in that: The sub-step S13 specifically includes: The hollow glass microspheres / ferrosoferric oxide are added to a mixed solution of a solvent, water and a weak base, and subjected to ultrasonic dispersion treatment; then ethyl orthosilicate is added, and stirred in a water bath to react to obtain a second precipitate; The second precipitate is cleaned with a second cleaning solution and then dried to obtain hollow glass microspheres / ferroferric oxide / silicon dioxide.
10. The method for preparing hollow glass microspheres / ferroferric oxide / carbon absorbing powder according to claim 9, characterized in that: The solvent includes anhydrous ethanol, and the weak base includes aqueous ammonia; The hollow glass microspheres / ferrosoferric oxide are 2 to 10 parts by mass, the anhydrous ethanol is 800 to 1200 parts by mass, the water is 200 to 500 parts by mass, the ammonia water is 20 to 100 parts by mass, and the tetraethyl orthosilicate is 1 to 6 parts by mass.
11. A hollow glass microsphere / ferroferric oxide / carbon absorbing powder prepared according to the preparation method of hollow glass microsphere / ferroferric oxide / carbon absorbing powder according to any one of claims 1 to 10, wherein the hollow glass microsphere / ferroferric oxide / carbon absorbing powder comprises a hollow glass microsphere layer as a hollow inner core layer, and a ferroferric oxide layer and a carbon layer sequentially coated on the outer surface of the hollow inner core layer from the inside to the outside, and there is a gap between the ferroferric oxide layer and the carbon layer.
Citation Information
Patent Citations
Method for preparing magnetically-supported catalyst TiO2 / polypyrrole (PPY) / Fe3O4
CN102580782A
Preparation method of hollow glass beads coated with nanometer Fe3O4
CN103043916A